PENGARUH KEPEMIMPINAN, MOTIVASI, PELATIHAN, DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PERUSAHAAN DAERAH AIR MINUM TIRTA MUSI KOTA PALEMBANG - Munparidi Munparidi (Orasi Bisnis : Jurnal Ilmiah Administrasi Niaga, 2012)
Assumption from this research reflected in hypothesis that suspects that there is a positive and significant influence from leadership, motivation, training, and working environment to performance. For testing the validity from that hypothesis it’s needed a related data from worker opinion about leadership, motivation, training, working environment, and performance. Data explored based one judgment and worker opinion from 81 respondents. The result of the regression analysis is meanwhile F is 29,809 with significant 0,00; R2 is 0,620. So the variable can explain 62% to performance and the rest 38% can be explained the other variables. From the research it can be concluded that training and working environment have positive influence to performance and then leadership end motivation have negative influence to performance.